ChemInform Abstract: Further Evidence for the Stabilization of U(V) within a Tetraoxo Core. Issue 29 (22nd July 2014) - Stritzinger, Jared T.; Alekseev, Evgeny V.; Polinski, Matthew J.; Cross, Justin N.; Eaton, Teresa M.; Albrecht‐Schmitt, Thomas E.
Abstract The new uranium borates K10 [(UO2)16(B2O5)2 (BO3)6O8]·7H2O (I) and K13 [(UO2)19(UO4) (B2O5)2 (BO3)6(OH)2O5] ·H2O (II) are isolated in 50% and 25% yield, resp., from reactions of UO3, KBO2, B2O3, and KOH in supercritical H2O (sealed Ag ampoules in autoclave, 600 °C, 4 d, ≈200 MPa).